2020
DOI: 10.3390/ijerph17207617
|View full text |Cite
|
Sign up to set email alerts
|

Work Schedule Irregularity and the Risk of Work-Related Injury among Korean Manual Workers

Abstract: Work schedules comprise various variables and generate health and safety outcomes, including work-related injury, which causes socioeconomic problems, such as productivity loss and damage to worker health. We investigated the association between work schedule irregularity and the incidence of work-related injury among South Korean manual workers using data from the 5th Korean Working Conditions Survey. In total, 18,330 manual workers were included. A multivariate logistic regression analysis was performed to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Considering some of the subscales on the HRQoL, the participants with moderate OPA were found to have better HRQoL than the individuals with high OPA including bodily pain, social functioning, and mental health. In a similar vein, previous studies have shown that occupational hazards are associated with jobs that placed heavy demands on both physical and mental capabilities [25,26]. This implies that the workers with high OPA were likely to be overworking and probably putting more pressure on their body system compared with those with moderate OPA.…”
Section: Discussionmentioning
confidence: 67%
“…Considering some of the subscales on the HRQoL, the participants with moderate OPA were found to have better HRQoL than the individuals with high OPA including bodily pain, social functioning, and mental health. In a similar vein, previous studies have shown that occupational hazards are associated with jobs that placed heavy demands on both physical and mental capabilities [25,26]. This implies that the workers with high OPA were likely to be overworking and probably putting more pressure on their body system compared with those with moderate OPA.…”
Section: Discussionmentioning
confidence: 67%
“…"Regular work schedule" was defined as a variable with fixed daily working hours, fixed weekly working days, fixed weekly work shift, and fixed start and end time of each shift, as indicated by the answers on the fifth KWCS. Work schedules that featured irregularity in any of the criteria were considered irregular [22].…”
Section: Work Regularitymentioning
confidence: 99%
“… 13 A total of 109,242 industrial accident victims and 2020 (1.8%) deaths occurred during this period. 14 The majority of these work-related injuries reportedly affected the upper limbs, lower limbs, and torso. 15…”
mentioning
confidence: 99%
“…13 A total of 109,242 industrial accident victims and 2020 (1.8%) deaths occurred during this period. 14 The majority of these work-related injuries reportedly affected the upper limbs, lower limbs, and torso. 15 Most studies on the frequency and cost of injury types sustained from industrial accidents have been conducted outside Korea.…”
mentioning
confidence: 99%
See 1 more Smart Citation